2013
DOI: 10.1515/revneuro-2012-0086
|View full text |Cite
|
Sign up to set email alerts
|

Red/near-infrared irradiation therapy for treatment of central nervous system injuries and disorders

Abstract: Irradiation in the red/near-infrared spectrum (R/NIR, 630-1000 nm) has been used to treat a wide range of clinical conditions, including disorders of the central nervous system (CNS), with several clinical trials currently underway for stroke and macular degeneration. However, R/NIR irradiation therapy (R/NIR-IT) has not been widely adopted in clinical practice for CNS injury or disease for a number of reasons, which include the following. The mechanism/s of action and implications of penetration have not been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
76
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(79 citation statements)
references
References 150 publications
(237 reference statements)
3
76
0
Order By: Relevance
“…However, R/NIR-IT has not been widely adopted in clinical practice for CNS injury, in part due to the large range of treatment fluences, irradiation time, wavelengths and devices cited in the literature making comparisons between studies difficult. As such, a consensus paradigm for treatment has not yet been established[48]. Here we report the outcomes of a multi-centre comparative study which shows that delivery of a defined number of photons at the surface of the skin overlying a CNS injury has differential effects on function and neuroprotection (as indicated by Tunel staining), depending upon the wavelength used to deliver the R/NIR-IT and the injury type.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, R/NIR-IT has not been widely adopted in clinical practice for CNS injury, in part due to the large range of treatment fluences, irradiation time, wavelengths and devices cited in the literature making comparisons between studies difficult. As such, a consensus paradigm for treatment has not yet been established[48]. Here we report the outcomes of a multi-centre comparative study which shows that delivery of a defined number of photons at the surface of the skin overlying a CNS injury has differential effects on function and neuroprotection (as indicated by Tunel staining), depending upon the wavelength used to deliver the R/NIR-IT and the injury type.…”
Section: Discussionmentioning
confidence: 99%
“…Irradiation between 600 and 1000 nm has better penetration because of reduced absorption at these wavelengths [48]. We demonstrate here that while the 830 nm R/NIR-IT array delivered an equal quantal dose to the surface of the skin (5.33×10 16 photons cm −2 s −1 ), the number of photons received at the SCI injury site was greater due to the increased penetrance of the longer wavelength R/NIR-IT through tissue (6.0×10 15 photons cm −2 s −1 for the 830 nm device compared to 3.5×10 15 photons cm −2 s −1 for the 670 nm device).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…35 There are currently 10 randomized clinical trials registered with the WHO International Clinical Trials Registry ranging from treating back pain, stroke and traumatic brain injury. Near-infrared therapy has been used in a number of smaller studies with no adverse effects and most recently has been shown to increase peripheral blood flow, 36 reduce osteoarthiritis in knee joints 37 and improve wound healing in chronic diabetic foot ulcers.…”
Section: Discussionmentioning
confidence: 99%